Demonstration of cytoplasmic and nuclear antigens in acute leukaemia using flow cytometry. Issue 9 (September 1994) - Farahat, N; van der Plas, D; Praxedes, M; Morilla, R; Matutes, E; Catovsky, D
Abstract : AIMS–To detect cytoplasmic and nuclear antigens using flow cytometry in acute leukaemia and to use this technique for double marker combinations. METHODS–Cytoplasmic staining was carried out in samples from 40 cases of acute leukaemia with monoclonal antibodies against the myeloid antigen CD13, the lymphoid antigens CD3, CD22, mu chain and the enzymes terminal deoxynucleotidyl transferase (TdT) and myeloperoxidase (MPO). The cells were fixed with paraformaldehyde and permeabilised with Tween 20 and Becton Dickinson's FACS lysing solution. Flow cytometry results were compared in the same cases with immunocytochemistry results using the alkaline phosphatase anti-alkaline phosphatase method. RESULTS–The gentle permeabilisation induced by this method permitted preservation of the membrane antigens and the size and morphology of the cells. The results using flow cytometry were comparable with those obtained using immunocytochemistry, with nearly complete concordance in most cases. CONCLUSIONS–This technique is simple, rapid, sensitive and reproducible and it is suitable for double staining procedures, such as nuclear and cytoplasmic, nuclear and membrane, or cytoplasmic and membrane. It therefore provides a powerful tool for extending the use of immunophenotyping for the diagnosis and follow up of acute leukaemia. It could also be used for the investigation of minimal residual disease.